Analysis Resilient Village of Merapi Volcano Eruption in Pusung Village, Boyolali Subdistrict, Boyolali District - Mochamad Dendy Arianto (Universitas Sebelas Maret, 2020)
Pusung Village located in the Merapi Volcano Foot. Based on the Kawasan Rawan Bencana (KRB) Map of Merapi Eruption in 2010, Pusung Village was included in KRB I. After the 2010 eruption, Pusung Village began to sister village disaster mitigation program. But in implementation, the disaster mitigation program with all aspects of village resilience to disasters has’nt been optimally. So, this study was conducted to determine the level of toughness Pusung Village and direction the implementation of village resilience. The method is scoring and SWOT analysis of questionnaires and observation. The results of this study are Pusung Village included Middle Disaster Resilient Village with the interaction SO is fulfillment sister village program requirements, the results of WO are disaster simulations be activated and need a balanced allocation, the result of ST is readiness in various aspects that can minimize disaster risk and the result of WT is balancing prevention services.